Ultrathin Nitrogen‐Doped Holey Carbon@Graphene Bifunctional Electrocatalyst for Oxygen Reduction and Evolution Reactions in Alkaline and Acidic Media. (14th November 2018) - Sun, Jiqing; Lowe, Sean E.; Zhang, Lijuan; Wang, Yazhou; Pang, Kanglei; Wang, Yun; Zhong, Yulin; Liu, Porun; Zhao, Kun; Tang, Zhiyong; Zhao, Huijun
Abstract: Efficient nonprecious‐metal oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) electrocatalysts are key for the commercial viability of fuel cells, metal–air batteries, and water‐splitting systems. Thus, high‐performance ORR and OER electrocatalysts in acidic electrolytes are needed to support high‐efficiency proton exchange membrane (PEM)‐based systems. Herein, we report a new approach to design and prepare an ultrathin N‐doped holey carbon layer (HCL) on a graphene sheet that exhibits outstanding bifunctional ORR/OER activities in both alkaline and acidic media. The edge sites of HCL are utilized to achieve selective doping of highly active pyridinic‐N. The sandwiched graphene sheet provides mechanical support, stabilizes HCL structure and promotes charge transfer. The synergetic effect of the catalyst structure overcomes the drawbacks of holey graphene approaches. The resulting ORR and OER performances are equal to or better than the top‐ranked electrocatalysts.